Heat capacity and thermodynamic functions of nano-TiO2 rutile in relation to bulk-TiO2 rutile. (February 2015) - Schliesser, Jacob M.; Smith, Stacey J.; Li, Guangshi; Li, Liping; Walker, Trent F.; Parry, Thomas; Boerio-Goates, Juliana; Woodfield, Brian F.
Graphical abstract: Highlights: Heat capacity data and thermodynamic properties for three TiO2 rutile nanoparticles of different hydration are presented. Water contributions were subtracted to yield thermodynamic properties of bare TiO2 rutile nanoparticles. These thermodynamic properties and those of bulk TiO2 rutile are equal within experimental error. Surface adsorbed water destabilizes the rutile phase in the nano-regime. Abstract: Several conflicting reports have suggested that the thermodynamic properties of materials change with respect to particle size. To investigate this, we have measured the constant pressure heat capacities of three 7 nm TiO2 rutile samples containing varying amounts of surface-adsorbed water using a combination of adiabatic and semi-adiabatic calorimetric methods. These samples have a high degree of chemical, phase, and size purity determined by rigorous characterization. Molar heat capacities were measured from T = (0.5 to 320) K, and data were fitted to a sum of theoretical functions in the low temperature ( T < 15 K) range, orthogonal polynomials in the mid temperature range (10 > T /K > 75), and a combination of Debye and Einstein functions in the high temperature range ( T > 35 K). These fits were used to generate Cp, m ∘, Δ 0 T S m ∘, Δ 0 T H m ∘, and φ m ∘ values at selected temperatures between (0.5 and 300) K for all samples. Standard molar entropies at T = 298.15 K were calculated to be (62.066, 59.422, and 58.035) J · K −1 · mol −1 all with a standard uncertainty of 0.002· Δ 0 T S m ∘ for samples TiO2 ·0.361H2 O, TiO2 ·0.296H2 O, and TiO2 ·0.244H2 O, respectively. These and other thermodynamic values were then corrected for water content to yield bare nano-TiO2 thermodynamic properties at T = 298.15 K, and we show that the resultant thermodynamic properties of anhydrous TiO2 rutile nanoparticles equal those of bulk TiO2 rutile within experimental uncertainty. Thus we show quantitatively that the difference in thermodynamic properties between bulk and nano-TiO2 must be attributed to surface adsorbed water.